Gear ratio optimization of single and two-speed transmission for an electric motorcycle - Jolana Hermanová (Acta Polytechnica CTU Proceedings, 2024)
Most electric vehicles have a single-speed transmission as the traction characteristic of an electric motor allows operation with sufficient motor torque at low and high speeds. Then, the selection of the single-gear ratio is a trade-off between available torque for acceleration (or gradability) at lower speeds and the designed maximum vehicle speed corresponding to the electric motor’s maximum speed limit. Nevertheless, the multiple-speed transmission can be used, and the vehicle can benefit from improved acceleration at low speeds and higher maximum speeds. In this paper, the gear ratio of a single-speed transmission for an electric racing motorcycle is optimized to achieve a trade-off between acceleration, lap time, and maximum speed. With the same goal, the gear ratios for two-speed transmission are optimized, and the results are compared.